A Asuhan Kebidanan Berkelanjutan (Continuity Of Care) Dalam Meningkatkan kesejahteraaan ibu dan bayi di TPMB EKA RINI: Asuhan Kebidanan Berkelanjutan (Continuity Of Care) Dalam Meningkatkan kesejahteraaan ibu dan bayi di TPMB EKA RINI - Eka Rini Kesumaningsih, Margaretha; Qurniasih, Nila; Ismiyati, Ismiyati; Mursiati, Sri (Jurnal Maternitas Aisyah (JAMAN AISYAH), 2024)
Background: The high MMR, IMR and CMR still show the main problems in midwifery services. Based on the 2023 Health Profile Report, MMR reached 189/100,000 live births, although there is a downward trend in maternal mortality, this is still far from the SDGs target of 70/100,000 live births by 2030. Obstetric complications are the biggest cause of MMR which further affects IMR. This is a serious problem in midwifery services, because high MMR can reduce the health status of a country. Therefore, efforts are needed to reduce the incidence of MMR and IMR. One of them is by applying the COC model. This care offers effective midwifery services, minimum intervention and provides midwifery services as needed, ranging from pregnancy, childbirth, newborn, postpartum to birth control. With this method, it is expected to create optimum maternal and infant welfare which further helps reduce MMR and IMR. Objective: To see the results of the implementation of the COC method in improving the welfare of mothers and babies during the prenatal, intranatal and postnatal periods. Method: The research was carried out observationally with a case study approach carried out on 3 research subjects in the third trimester of pregnancy, who were followed from the start of pregnancy to family planning. Sampling was carried out at TPMB, data collection was carried out by analyzing data through mentoring formats, interviews and observation. Results: Based on care, the COC care model can help normal pregnancy and delivery, minimum intervention and proven to be able to overcome discomfort problems in clients. Suggestion: The COC care model can be applied in midwifery services